The Impact of the Change in the Exchange Rate of the US dollar on the Trade Balance: Algeria Case Study - Econometric Study (1990 - 2016) - MOKHTARI, Fatiha; CHENIKHAR, Abdelouahab (Journal of Finance & Corporate Governance, 2018)
This research study aims at assessing the impact of the Algerian Dinar exchange rates variations on the Algerian trade balance during the period from 1990 to 2016.To achieve such an aim, we adopted a measuring model that suits local economy reality. The chosen model assessment was carried out by means of the OLS method and the cointegration test to notice if there are long term relationship between the dependent variable and interpreting ones. Econometrics analysis showed that exchange rate variations have negative impact on trade balance as an inverse relationship exists between exchange rate variations and trade balance, which is the exact opposite of what is stated by economic theory, the cointegration test showed no relations at all between dependent and interpreting variables in the long run. We concluded that Granger causality test gave results which rule out any causal relationship between dependent and independent variables as immediate response functions test showed weak trade balance response to any shock due to exchange rate variations of the local currency during the studied period.